Sex Equality in Family Law: Historical Legacies, Feminist Activism, and Religious Power in 70 Countries - Htun, Mala (Washington, DC: World Bank, 2012)
Family law--also called personal status law--is one of the central institutions of gender. It molds social identities and distributes rights and responsibilities, forging relations of power between men and women, parents and children, brothers and sisters. These status differences are consequential not just for the private sphere but also for public opportunities. Family laws shape the capacity of a citizen to own, inherit, and manage property; to work outside the home; her freedom to marry, divorce, and remarry; and her or his relationship with children. Most modern family law emphasizes patriarchy and other forms of male dominance. It tended (and still tends) to maximize men's power over women and limit the latter's ability to make decisions and take independent action. Classical Islamic law, the Napoleonic Code, Anglo-American common law, and the customary law of many sub-Saharan African groups and indigenous peoples of the Americas all upheld the notion that men were in charge of family life: they controlled property, were the legal guardians of children, and had the right to restrict their wives' public activities. Women were obliged to obey their husbands, had limited access to divorce, and, in many traditions, fewer inheritance rights than men.